Comparative evaluation of diffusion hypoxia and psychomotor skills with or without postsedation oxygenation following administration of nitrous oxide in children undergoing dental procedures: A clinical study - Vineet Inder Singh Khinda; Parvesh Bhuria; Paramjit Khinda; Shiminder Kallar; Gurlal Singh Brar (Wolters Kluwer Medknow Publications, 2016)
Background: Diffusion hypoxia is the most serious potential complication associated with nitrous oxide. It occurs during the recovery period. Hence, administration of 100% oxygen is mandatory as suggested by many authors. Aim: The aim of this study is to evaluate the occurrence/nonoccurrence of diffusion hypoxia in two groups of patients undergoing routine dental treatment under nitrous oxide sedation when one group is subjected to 7 min of postsedation oxygenation and the second group of the patients is made to breathe room air for the similar period. Materials and Methods: A total of sixty patients within the age group of 7-10 years requiring invasive dental procedures were randomly divided into two groups of 30 each using chit method. In the control group, patients were administered 100% oxygen postsedation, whereas, in the study group, patients were made to breathe room air postsedation. Various parameters (pulse rate, respiratory rate, blood pressure, and oxygen saturation [SpO2]) were recorded pre- and post-operatively. Data were collected and then sent for statistical analysis. Results: The mean postoperative SpO2 at measurement times 1, 3, 5, and 7 min in both the groups was higher than the mean preoperative SpO2. This increase was statistically significant. No significant difference was found between the Trieger test scores. Conclusion: This study proves that clinical occurrence of diffusion hypoxia is not possible while following the routine procedure of nitrous oxide sedation.